PERSEPSI TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KORUPSI ANGGARAN PENDAPATAN DAN BELANJA DAERAH - Wijaya, Anthonius H. Citra (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
The study aims to analyze and test hypotheses regarding the influence of individual behavior, internalÂ oversight and ethical Culture of the Organization against the corrupt tendencies of the regional budget revenue and expenditure (APBD). Respondents in this study were students of the accountingÂ study Program at several universities located in Jayapura City. In this study the sampling methodÂ used Purposive sampling. The Data Analysis method used is multiple regression analysis and testingÂ tools using SPSS 24. The results showed that the individual behavior variables of influential internalÂ supervision were not significant to the tendencies of the fraud/corruption behavior OF THE APBD. InÂ addition, the organization's ethical cultural variables have a significant positive impact on theÂ behavioral tendencies of APBD corruption.